De l'«Homo sapiens» a l'animal metafòric - Teruel Planas, Elvira (Caplletra. Revista Internacional de Filologia, 2000)
Elvira Teruel offers a wiew of metaphor as a natural device of human cognition instead of a pure ornamental tool. Metaphor is then shown as a factor of meaning construction pervasive across different kinds of discourse, including conversation and jounalistic discourse.